2021
DOI: 10.1227/ons.0000000000000050
|View full text |Cite
|
Sign up to set email alerts
|

Frameless Robotic-Assisted Deep Brain Stimulation With the Mazor Renaissance System

Abstract: BACKGROUND: Robotic-assisted stereotactic systems for deep brain stimulation (DBS) have recently gained popularity because of their abilities to automate arduous human error-prone steps for lead implantation. Recent DBS literature focuses on frame-based robotic platforms, but little has been reported on frameless robotic approaches, specifically the Food and Drug Administration-approved Mazor Renaissance Guidance System (Mazor Robotics Ltd). OBJECTIVE: To present an initial case series for patients undergoing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…5,17-23 Four studies reported their use of a skull-mounted robot with optical array registration/navigation, with a target radial error of 1.12 ± 0.54 mm (n = 406 electrodes), operative time of 155.4 ± 36.5 minutes (n = 406), and total procedure time of 277.1 ± 38.2 minutes (n = 165). 7,24-26 Three studies (including this study) reported the use of a floor-mounted robot with a frameless transient fiducial array, with a target radial error of 0.84 ± 0.54 mm (n = 631 electrodes), operative time of 182.4 ± 47.8 minutes (n = 315), and total procedure time of 311.9 ± 63.0 min (n = 315). 27,28 One study reported their use of a floor-mounted robot with optical registration, and the only metric recorded was target radial error: 1.28 ± 0.37 (n = 60 electrodes).…”
Section: Resultsmentioning
confidence: 99%
“…5,17-23 Four studies reported their use of a skull-mounted robot with optical array registration/navigation, with a target radial error of 1.12 ± 0.54 mm (n = 406 electrodes), operative time of 155.4 ± 36.5 minutes (n = 406), and total procedure time of 277.1 ± 38.2 minutes (n = 165). 7,24-26 Three studies (including this study) reported the use of a floor-mounted robot with a frameless transient fiducial array, with a target radial error of 0.84 ± 0.54 mm (n = 631 electrodes), operative time of 182.4 ± 47.8 minutes (n = 315), and total procedure time of 311.9 ± 63.0 min (n = 315). 27,28 One study reported their use of a floor-mounted robot with optical registration, and the only metric recorded was target radial error: 1.28 ± 0.37 (n = 60 electrodes).…”
Section: Resultsmentioning
confidence: 99%
“…Bunyaratavej et al [26] reported that the error was significantly larger for the second implant, usually in the antero-posterior direction. Liang et al [19] also reported error of the second implant (right side) was much larger than that of the first implant (left side) when using frameless robot system. The error might be a consequence of brain shift that results from cerebrospinal fluid (CSF) loss and pneumocephalus that occurs after surgery, especially after more manipulation of patients with macrostimulations [27,28].…”
Section: Discussionmentioning
confidence: 95%
“…In recent reports of errors achieved with other robot-assisted DBS, mean radial errors ranged from 0.6 to 1.7 mm and most studies comparing errors with the classic method showed better non-inferior outcomes in robot groups; the errors from other robot-based DBS surgeries are shown in Table 2 [12][13][14][15][16][17][18][19][20][21][22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%